Comparison of 12-month clinical outcomes in diabetic and nondiabetic patients with chronic total occlusion lesions: a multicenter study. Issue 8 (December 2015) - Rha, Seung-Woon; Choi, Cheol Ung; Na, Jin Oh; Lim, Hong Euy; Kim, Jin Won; Kim, Eung Ju; Park, Chang Gyu; Seo, Hong Seog; Oh, Dong Joo; Gwon, Hyeon-Cheol; Kim, Byeong-Keuk; Kim, Hyo-Soo; et al.
Abstract : Objective: This study aimed to compare 1-year clinical outcomes in diabetic and nondiabetic patients with chronic total occlusion (CTO) lesions. Methods: A total of 2865 patients (age 62.82±10.64 years; 74.0% men) undergoing percutaneous coronary intervention for CTO were analyzed. The patients were classified as diabetic ( n =977) or nondiabetic ( n =1888). One-year clinical outcomes were compared between the two groups. Results: One year after percutaneous coronary intervention, 241 (8.4%) patients developed major adverse cardiac events (MACEs). Target lesion revascularization (TLR), target vessel revascularization (TVR), TLR-MACEs, and total MACEs were more common in diabetics than in nondiabetics (6.1 vs. 3.9%, P =0.021; 7.2 vs. 4.8%, P =0.023; 7.7 vs. 5.5%, P =0.017; and 10.3 vs. 7.7%, P =0.011; respectively). In multivariate analysis, diabetes mellitus was an independent predictor for 1-year TLR (odds ratio: 2.201, P =0.001) and total MACEs (odds ratio: 1.677, P =0.002). Among diabetic patients, total death, TLR, TVR, TLR-MACEs, TVR-MACEs, and total MACEs were more common in patients who used insulin than in those who did not (6.1 vs. 1.9%, P =0.018; 11.3 vs. 4.6%, P =0.007; 12.2 vs. 5.9%, P =0.025; 14.8 vs. 5.9%, P =0.003; 16.5 vs. 8.0%, P =0.008; and 17.4 vs. 9.2%, P =0.012, respectively). Insulin use was an independent predictor for total death, 12-month TLR, TVR, TLR-MACEs, TVR-MACEs, and total MACEs. Conclusion: This study identified diabetes mellitus as an independent risk factor for 1-year TLR and total MACEs in patients with CTO lesions. Abstract : Supplemental Digital Content is available in the text.